ANTICIPATING VERBAL ABUSE IN YOUNG CHILDREN THROUGH A CULTURE OF POLITE LANGUAGE - Mia Revi Ukhtiani; Farida Ariyani Kangiden; Arip Arizal Mustahidin (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2025)
Polite language is reflected in the manner of communication through verbal signs or language usage. When communicating, we are subject to cultural norms, not just conveying the ideas we think of. Language usage must be in accordance with the cultural elements that exist in the community where a language is used for communication. The type of research used in this study is qualitative research involving a literature study. The informants in this study were three female teachers and three parents/mothers from Al-Husna Argodadi Early Childhood Education Center in Yogyakarta. In this study, the author used interviews as a data collection instrument, while data analysis was performed using Nvivo software. This study aims to determine the politeness of language in combating verbal abuse against children. The results of interviews conducted by the researcher with teachers and parents show that polite language is used to combat verbal abuse against children by providing an understanding of appropriate language and polite sentences, and introducing children to which languages are acceptable and unacceptable to use, as well as practicing educational and empathetic communication. Parents and teachers play a crucial role in setting an example and providing ongoing guidance so that children can discern and use language appropriately to achieve their intended meaning in a healthy manner.